Professional Ethics Training and the Graduate Professors in the National Autonomous University of Mexico - Ana Hirsch Adler (Universidad Autónoma de Baja California, 2010)
The purpose of the article is to present the results obtained with a sample of 704 professors of the forty graduate programs in UNAM, with the open question: Do you consider that a subject about professional ethics should be included for all students?, with which contents? This question is part of an instrument applied in 2006 and 2007. The majority expressed that it should exist a special subject about professional ethics. All the answers were codified in four categories. We introduced two other sources of information: the answers to the same question asked in 2004 to 11 professors from different universities in Spain, and three training proposals given by the professors interviewed.